The rule of peshat : Jewish constructions of the plain sense of scripture in their Christian and Muslim contexts, 900-1270 - Cohen, Mordechai Z. (University of Pennsylvania Press, 2020)
This book looks at the peshat mode of reading the Bible (as opposed to the midrashic mode). The mode was present in the tenth to twelfth centuries. Peshat is the plain meaning of the text, the plain reading, the philological reading, the nonmystical reading. Our author explores how the peshat mode influenced Christian and Muslim schools of interpretation and vice versa; and how the peshat scholars broke from the midrashic mode of biblical interpretation. Spain, France, and the Middle East were important centers for the peshat mode"-- Provided by publisher.
Description based upon print version of record.
Keywords: Bible. -- Old Testament -- Criticism, interpretation, etc., Jewish -- History -- To 1500.; Bible. -- Old Testament -- Criticism, interpretation, etc. -- History -- To 1500.; Bible. -- Old Testament -- Islamic interpretations -- History -- To 1500.; Bible. -- Old Testament -- Commentaries -- Early works to 1800.; Bible. -- Old Testament; RELIGION / Biblical Criticism & Interpretation / Old Testament; Islamic interpretations of sacred works; To 1500; Criticism, interpretation, etc.; Early works; History